Parasitic Worm Infection amongst the Orang Asli (aboriginal)School Children near Cyberjaya, Malaysia - Noor Amiza Zainal Abidin; Wan Omar Abdullah; Mohamed Kamel AG; Zatul-'Iffah Abu Hasan; Faizul Helmi Addnan; Nur Fariha Mohd Manzor; Noradilah Samseh Abdullah; Fadlul Azim Fauzi Mansur (Japan Health Sciences University & Japan International, 2024)
Non-Indexed Publication